The effect of Service Quality on Outpatient Satisfaction at RSAU Lanud Sulaiman Bandung - Sasmita, Oktavia; Fauzan Azhmy, Muhammad; Syahyunan, Syahyunan (Sumber Belajar Sejahtera, 2024)
This type of research is quantitative research with survey methods, a cross sectional approach, and an explanatory research level. Data was obtained by respondents by filling out questionnaires using closed questionnaire techniques. With five dimensions of service quality as independent variables and patient satisfaction as the dependent variable. The population in this study were outpatients at RSAU Lanud Sulaiman, Bandung. The sample used was 94 people. The analysis used is descriptive analysis and inferential analysis which includes: multiple linear regression analysis, T test, F test, and coefficient of determination. The research results show that service quality in terms of tangible, reliability, responsiveness, assurance and empathy dimensions together (simultaneous) have a positive and significant effect on patient satisfaction . The multiple linear regression equation shows the variable relationship pattern. The partial analysis results show that the variable reliability with P value of 0.00<0.05, responsiveness with P value of 0.027<0.05, assurance with P value of 0.000<0.05 and empathy with P value of 0.000<0.05 which shows positive and significant influence on patient satisfaction, however tangible variables have a positive but not significant influence on patient satisfaction, as indicated by the P value 0.324>0.05. The results of the Standardized Coefficient Beta test show that the variable that has the most dominant influence on patient satisfaction is the empathy variable with β value of 0.691. Meanwhile, the coefficient of determination test shows that service quality influences patient satisfaction by 87.6%, and the remainder is influenced by other factors not studied.